Effects on congestion, natriuretic peptides, diuretic efficiency, and renal function during different dose and administration of intravenous loop diuretic: preliminary data of DIUR-AHF Trial. (25th November 2020) - Ruocco, G; Evangelista, I; Brazzi, A; Luschi, L; Feola, M; Iacoviello, M; Passantino, A; Palazzuoli, A
Abstract: Background: Although loop diuretic is the cornerstone of treatment in acute heart failure (AHF) there is no consensus about the best modality and amount to be used during acute phase. Current Guidelines do not provide specific insights regarding timing course and target dose. Usually physicians double the oral domestic amount when they start intravenous infusion, but a precise algorithm does not exist. Aims: To compare admission and pre discharge clinical congestion and BNP trend in relation to furosemide amount and modality administration; 2- to evaluate diuretic efficiency and renal function in the four arms and the potential effects on outcome. Methods: This is a multicentre prospective Trial (DIUR-AHF) designed in order to clarify the correct loop diuretic target avoiding potential side effects. The study enrolled patients with AHF BNP level >100 pg/ml and congestion signs. Patients were divided in four arms in accordance with modality administration: Continuous (Ci) vs Bolus (Bi) and dose administered Low (LD) vs High (HD) considering a cutoff 125 mg/die. All patients executed a clinical congestion evaluation and Chest radiography at admission and pre discharge, BNP sample and renal function were measured during the first 12 hours and before discharge. Diuretic efficiency (DE) defined as weight change per 40 mg of furosemide during infusional period. DE was estimated as the net fluid output produced per 40 mg of furosemide equivalents, Follow up were obtained by direct visit or phone contact at 30 and 60 days after discharge Results: We included 268 hospitalized patients with a mean BNP level 987±440 pg /ml, mean congestion score (3.5±2) creatinine and GFR value were 1.6±0.7 mg/dl; and 48±20 ml/min/m 2 respectively. At admission BNP and Creatinine were modestly increased in HD (P<0.01) compared with all other groups. Pre discharge Congestion score were increased in Bi and HD groups (2.5±1 vs 1±1), similarly BNP levels were increased in Bi and HD with respect to Ci and LD (454±215 and 413±223 vs 288±170 and 312±248 p<0.05). Whereas DE were significantly increased in Ci compared with the other arms (−1.23 vs −0.55 p<0.01). In all groups, low DE, residual congestion and BNP reduction <30% resulted in escalation of diuretic strategies and impaired outcome (HR 1.88 [1.16–204]; 2.1 [1.4–2.8]; 1.3 [0.88–2.1]). A significant correlation between poor DE and residual congestion was recruited (r=0.76). Worsening Renal function (WRF) occurred much more in HD and Ci compared to LD and Bi (HD 44%, Ci 35% vs LD 33% and Bi 23% p<0.01) without significant effects on outcome. Conclusions: HD and Bi of furosemide are both related with reduced congestion and invreased BNP level before discharge. In all groups low DE residual congestion and poor BNP reduction appear associated with higher rate of adverse events. Current data provide additional features for AHF patients during intravenous loop diuretic administration Funding Acknowledgement: Type of funding source: None